Polybrominated diphenyl ethers perturb axonal growth and actin distribution - Neupane, Bhanu B; Jin, Tao; Gu, Zhen; Ligler, Frances S; Wang, Gufeng (BIBECHANA, 2018)
We investigated toxicological effects of two of the most common polybrominated diphenyl ether (PBDE) flame retardants, BDE-47 and BDE-209, in model PC12 cell line under two environmentally relevant exposure conditions: long term exposure to microgram-per-liter levels of PBDEs and acute exposure to high concentrations of PBDEs. Cells treated under both long term and acute exposure conditions showed significantly perturbed cell growth and differentiation. Importantly, even when the cells were exposed to microgram-per-liter concentration of PBDEs over an extended period, both the fraction of differentiated cells and the axonal growth were affected. The calcium release assay showed that PBDEs perturbed intracellular calcium release in a concentration dependent manner, indicating that intracellular Ca++ homeostasis and signaling was involved in the neurotoxicity. More interestingly, depending on PBDE concentration and exposure conditions, cytoskeleton F-actin distribution was altered. BIBECHANA 16 (2019) 64-78